2024
DOI: 10.1007/s00068-024-02472-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients with proximal femur fractures under DOACs

Marc Maegele

Abstract: Purpose In the past, preinjury direct oral anticoagulant (DOAC) intake has led to delays in time to surgery (TTS) in patients with proximal femur fractures and delays in surgery have been associated with impaired outcomes. Although healthcare institutions/federal committees have set rules for treatment within 24 h of injury, comprehensive guidelines for the perioperative management of these patients, in particular when on preinjury DOACs, are still lacking. This contribution aims to summarize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Thus, it was concluded that it is unnecessary to delay surgery for patients with PFF who are treated with platelet aggregation inhibitors. As no comprehensive guidelines for the perioperative management of patients under current treatment with direct oral anticoagulants (DOAC) are available, Marc Maegele summarizes the current evidence on the safe time window for surgery in patients in patients with PFF [ 6 ]. Furthermore, the author outlines the possible therapeutic options if emergency DOAC reversal becomes necessary.…”
mentioning
confidence: 99%
“…Thus, it was concluded that it is unnecessary to delay surgery for patients with PFF who are treated with platelet aggregation inhibitors. As no comprehensive guidelines for the perioperative management of patients under current treatment with direct oral anticoagulants (DOAC) are available, Marc Maegele summarizes the current evidence on the safe time window for surgery in patients in patients with PFF [ 6 ]. Furthermore, the author outlines the possible therapeutic options if emergency DOAC reversal becomes necessary.…”
mentioning
confidence: 99%